Correlação entre alterações nucleares de espermatozoides de touro identificados por microscopia eletrônica de transmissão e a eficiência na produção in vitro de embriões - Alves, Paulo Henrique Mazzutti (2016)
Sperm chromatin changes has been studied in several animal species to be considered an important factor related to infertility that impair the results of reproductive biotechnologies. The aim of this work was to verify the bovine sperm chromatin changes in transmission electron microscopy, classifying and correlate them with the results of in vitro embryo production (IVP). Crossbred cattle between 30 and 36 months were subjected to scrotal insulation for 72 hours and ejaculates were collected weekly for 60 days. Semen samples of ejaculates were processed and chromatin changes evaluated in transmission electron microscopy and classified into 5 categories according to the intensity of the change. IVP routines were performed weekly to evaluate cleavage and blastocyst rates when using these ejaculates. The results of IVP routines were not correlated with the chromatin changes evaluated in transmission electron microscopy. The few spermatozoa found with more intense changes in chromatin also had morphology changed. Small light dots were found very frequently near to the insertion of the flagellum. It is concluded that when evaluating between 100 and 200 images of sections of sperm heads per ejaculate in transmission electron microscopy, it was not possible to verify the influence of chromatin changes in the results of IVP.